2021
DOI: 10.3390/en14041047
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of High Renewable Energy Sources Integration in Power Systems—The Case of Croatia

Abstract: This paper presents a high-level overview of the integration of renewable energy sources (RES), primarily wind and solar, into the electric power system (EPS) in Croatia. It presents transmission system integration aspects for the particular case of this country. It explains the current situation and technical characteristics of the current conventional generation units and currently installed wind energy capacities. Based on the current situation future development scenario is determined and used to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In view of the difficulty of grid-connected scheduling of large-scale wind farms, the authors in [24] proposed a virtual power plant concept that equivalently aggregates wind turbines in a certain area with conventional water, thermal power units and energy storage equipment, and realizes the power grid power for the unit equipment in the area. Reference [25] discussed the problems and possible solutions of access to clean energy such as wind power in view of existing power environment, but did not give specific solutions and analysis. Reference [26] proposed a day-ahead clearing model for the power pool market considering wind power, drawing on the idea of "ex-post electricity price", and generating a multi-scenario model based on the results of probabilistic wind power forecasting, taking into account the economy and safety of system operation.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the difficulty of grid-connected scheduling of large-scale wind farms, the authors in [24] proposed a virtual power plant concept that equivalently aggregates wind turbines in a certain area with conventional water, thermal power units and energy storage equipment, and realizes the power grid power for the unit equipment in the area. Reference [25] discussed the problems and possible solutions of access to clean energy such as wind power in view of existing power environment, but did not give specific solutions and analysis. Reference [26] proposed a day-ahead clearing model for the power pool market considering wind power, drawing on the idea of "ex-post electricity price", and generating a multi-scenario model based on the results of probabilistic wind power forecasting, taking into account the economy and safety of system operation.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [16] performed a case study on the reactive power management of a PV integrated cogeneration power plant to determine the effects of higher PV integrations and protection issues [17] and suggested certain guidelines for RE integration. The authors in [18] have studied the challenges with high RE penetration of Croatia and confirmed that even a 30% RE penetration itself will cause voltage and frequency problems. They have suggested to adopt novel methodologies to mitigate the higher RE penetration effects.…”
Section: Literature Surveymentioning
confidence: 93%
“…As global environmental problems become more salient, many countries have put forward and vigorously advocated renewable, pollution-free new energy generation. To respond to international calls and meet the increasing demand for electric power, renewable energy and power electronic equipment have been widely applied in the electric power industry (Harker Steele et al, 2021;Holjevac et al, 2021;Zhang Z. et al, 2022), and the power network's capacity to absorb new energy power generation has also been continuously improved. However, because of some characteristic restrictions and technical limitations such as unstable output, poor controllability, and complex structure, new energy and power electronic equipment do not participate in conventional frequency regulation tasks temporarily, which will undoubtedly reduce the frequency support capacity of the power network in the same proportion (Zhao D. et al, 2019;Meegahapola et al, 2020;Ouyang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%